Martin Lebowitz papers - Lebowitz, Martin, 1921-1993.
Correspondence, photographs, death announcement, and eulogy relating primarily to Lebowitz's work as a philosopher and critic. Includes material from his undergraduate years at Columbia University, New York, N.Y. Correspondents include Jacques Barzun, Leon Edel, Doris Grumbach, David Madden, Iris Murdoch, John Crowe Ransom, Diana Trilling, and Lionel Trilling.
Critic and philosopher.
Collection material in English.
Keywords: Barzun, Jacques, -- 1907-2012 -- Correspondence; Edel, Leon, -- 1907-1997 -- Correspondence; Grumbach, Doris -- Correspondence; Madden, David, -- 1933- -- Correspondence; Murdoch, Iris -- Correspondence; Ransom, John Crowe, -- 1888-1974 -- Correspondence; Trilling, Diana -- Correspondence; Trilling, Lionel, -- 1905-1975 -- Correspondence; Columbia University -- Students; Criticism; Philosophy; Critics; Philosophers